The Activities of Motiejus Valančius from the Viewpoint of Political Philosophy - Jokubaitis, Alvydas (Problemos, 2014)
The aim of the article is to look into the activities of Motiejus Valančius from the perspective of political philosophy. Historians acknowledged that Valančius had created a separate epoch in Lithuanian history, however, they have not revealed the distinctive qualities that are definitive of the content of this period. Political philosophy is helpful in attempting to accomplish this task. One has to begin from available historical research and search for new concepts that would provide an explanation of the activities of Valančius. It is argued in the paper that the Samogitian episcopate that was governed by Valančius was the first political form of modern Lithuanian nation – an intermediate stage between the Grand Duchy of Lithuania and the nation state. Valančius was managing the institution that had a political meaning and created a distinct historical chapter which can be described as interregnum.